Trajectories of Growth and Serum DHEAS and IGF-1 Concentrations in Girls With a History of Premature Adrenarche: Attenuation of the Phenotype by Adulthood - Liimatta, Jani; Utriainen, Pauliina; Voutilainen, Raimo; Jääskeläinen, Jarmo (Frontiers in Endocrinology, 2018)
Background: It has been speculated that premature adrenarche (PA) could lead to unfavorable outcome, including shorter adult stature, but longitudinal follow-up data are insufficient. Methods: This prospective case-control study included 30 PA and 42 control females who were born mostly full-term and appropriate for gestational age. They were examined first at the median age of 7.6 years and now at 18.1 years. Main outcome measures were height, body mass index (BMI), age at menarche, and serum dehydroepiandrosterone sulfate (DHEAS) and insulin-like growth factor 1 (IGF-1) concentrations. Results: The PA and control females had comparable mean (standard deviation) adult height (167.2 (6.8) vs 164.5 (5.1) cm, P = 0.059) and median (interquartile range) BMI (22.8 (21.1-28.9) vs 21.6 (19.8-24.3) kg/m2, P = 0.068, respectively). Adult heights were comparable with the mid-parental heights in both study groups. The PA females were taller than the controls until the age of 12 years and they lacked a distinct pubertal growth spurt. Serum DHEAS and IGF-1 concentrations did not differ between the PA and control groups at the age of 18 years. Median (range) age at menarche was significantly lower in the PA than control females (11.5 (9.5-15.0) vs 13.0 (10.0-15.0), P = 0.001). Conclusions: Although PA girls have advanced growth and earlier pubertal development together with a tendency to be more overweight, their height, BMI, and serum DHEAS and IGF-1 concentrations are comparable to those of their peers at the age of 18 years. Our findings indicate a benign outcome of PA in appropriate for gestational age -born females concerning adult height and adrenal androgen secretion.